Black carbon aerosol and its radiative impact at a high‐altitude remote site on the southeastern Tibet Plateau. Issue 10 (22nd May 2017) - Zhao, Zhuzi; Wang, Qiyuan; Xu, Baiqing; Shen, Zhenxing; Huang, Rujin; Zhu, Chongshu; Su, Xiaoli; Zhao, Shuyu; Long, Xin; Liu, Suixin; Cao, Junji
Abstract: Aerosol black carbon (BC) was measured with an Aethalometer™ at Lulang, a high‐altitude station in southeastern Tibetan Plateau (TP), from July 2008 to August 2009. Daily mean BC loadings varied from 57.7 to 5368.9 ng m −3 (grand average ± standard deviation = 496.5 ± 521.2 ng m −3 ), indicating a significant BC burden even at free tropospheric altitudes. BC loadings were highest during the premonsoon and lowest during the monsoon, and peaks in BC were coincident with high atmospheric boundary layers. Daily peaks in BC occurred from 08:00 to 10:00 local time with minor fluctuations at other times. The BC mass absorption efficiency (MAE) was calculated from elemental carbon concentrations obtained from a thermal/optical reflectance method and absorption coefficients from the Aethalometer™, and values ranged from 6.1 to 31.7 m 2  g −1 (average = 16.6 ± 5.7 m 2  g −1 ). Strong variations in the MAEs during the monsoon can be ascribed to large uncertainties due to low BC and b abs and possibly coatings on the BC. High MAEs during premonsoon pollution events were likely due to internal mixing during transport. The mean direct surface radiative forcing (DRF) estimated from a radiation model was −19.9 (±7.4) W m −2 for the full aerosol population and −3.9 (±1.8) W m −2 for a BC only scenario. The BC DRF during a case study (−36.0 W m −2 ) was much stronger than the typical, and the BC contribution to the forcing was higher (~50%) than usual (~20%). These results show that BC can at times account for a relatively large fraction of the aerosol surface heating over the southeast TP, which may affect both climate and hydrological cycles. Key Points: Light absorption measurements were carried out at a high‐altitude site in southeast Tibet Peaks in BC were coincident with deeper atmospheric boundary layers During pollution events BC DRF contributed to the total atmospheric forcing was significantly higher (~50%) than usual (~20%)